Pengaruh Ukuran Biji Kopi dan Lama Penyangraian Terhadap Mutu Organoleptik Kopi Liberika Tungkal Komposit - Vionita, Diny; Marpaung, Ridawati; Hartawan, Rudi (Jurnal Media Pertanian, 2025)
The purpose of this study was to determine the effect and interaction between coffee bean size and roasting time on the organoleptic quality of brewed Liberika coffee powder. This research was conducted in Betara District, West Tanjung Jabung Regency and Basic Laboratory of the Faculty of Agriculture, Batanghari University, conducted in November 2024 - January 2025. This study used a factorial complete randomized design, the first factor of liberica coffee bean size consisted of 3 levels, namely size S (k1), M (k2) and L (k3) while the second factor of roasting time consisted of 2 levels, namely roasting time of 25 minutes (w1) and roasting time of 30 minutes (w2), so that 6 treatment combinations were obtained, where each treatment was repeated 3 times, resulting in 18 experimental units. The study's variables included chemical characteristics, including acidity (pH), and organoleptic characteristics, such as colour, flavour, aroma, bitterness, and preference for brewed coffee powder. The findings demonstrated that the pH of coffee powder and the organoleptic qualities of colour, aroma, taste, bitterness, and liking of brewed coffee powder were not significantly impacted by coffee bean size or roasting time. The results of organoleptic testing of untrained panelists gave the best impression of liking to brewed coffee powder with coffee bean size L (k3) and roasting time of 30 minute.